An interval two-stage fuzzy fractional programming model for planning water resources management in the coastal region – A case study of Shenzhen, China. (1st August 2022) - Li, Xiaoyang; Huang, Guohe; Wang, Shuguang; Li, Yongping; Zhang, Xiaoyue; Zhou, Xiong
Abstract: In this study, an interval two-stage fuzzy fractional programming (TFFP) method is developed to facilitate collaborative governance of economy and water resources. Methods of interval programming, fuzzy programming, two-stage programming, and fractional programming are integrated within a general system optimization framework. The main contribution of TFFP is simultaneously addressing various uncertainties and tackling trade-offs between environmental and economic objectives in the optimized schemes for water resources allocation. A case study of a highly urbanized coastal city (i.e., Shenzhen) in China is provided as an example for demonstrating the proposed approach. According to the results, industrial sectors should receive 34.8% of total water supply, while agricultural sectors should receive 1.5%. For the spatial allocation of water resources, Bao An, Long Gang, and Fu Tian districts should be allocated 21.6%, 20.5%, and 14.8% water to promote the economic development. The discharge analysis indicates that chemical oxygen demand (CODcr ) and total phosphorus (TP) would be key pollutants. Moreover, the optimized seawater desalination volume would be negligibly influenced by price, while the upper bounds of desalination would be increased with the raising acceptable credibility levels in the period of 2031–2035. Analysis of desalination prices also reveals that the decision-makers should increase the scale of desalination in the period of 2021–2025. In addition, the effectiveness and applicability of TFFP would be evaluated under economic maximization scenarios. The result showed that the economic maximization scenario could obtain higher economic benefits, but it would be accompanied by a larger number of pollutant discharges. It is expected that this study will provide solid bases for planning water resources management systems in coastal regions. Graphical abstract: Image 1 Highlights: An interval two-stage fuzzy fractional programming (TFFP) method is developed. TFFP examines desalination issues within a water resources optimization framework. Uncertainties and associated social-economic and environmental risks are quantified. Trade-offs among environmental and economic objectives are revealed. TFFP can facilitate management water resource systems in coastal regions.